HOX transcript antisense RNA is elevated in gastric carcinogenesis and regulated by the NF‐κB pathway. Issue 6 (11th January 2019) - Zhang, Zhun; Fan, Bingbing; Liu, Fengyan; Song, Ning; Peng, Yanping; Ma, Wenzheng; Ma, Rongtao; Dong, Tianyi; Liu, Shili
Abstract: The expression pattern of HOX transcript antisense RNA (HOTAIR) in the progression of gastric cancer and the regulation of its expression are still unclear. In the current study, HOTAIR expressions in gastric tissues collected from patients with superficial gastritis, atrophic gastritis, atypical hyperplasia, and gastric cancer as well as normal controls was quantitatively examined. The results showed that the expression of HOTAIR was higher in gastric cancer than in normal tissues, but reached the highest level in atrophic gastritis, suggesting that HOTAIR may be involved in the molecular process of nonresolving inflammation. Then tumor necrosis factor‐α‐induced protein‐8 like‐2 (TIPE2), a known gene associated with nonresolving inflammation, was overexpressed and the results showed that the promotion in TIPE2 expression triggered HOTAIR reduction, this result was further verified by microarray analysis and TIPE2 knockout mice. Subsequently, the data obtained from HOTAIR knockdown experiment showed that it significantly enhanced colony forming capability and inhibited p27 expression in AGS cells. Furthermore, deletion constructs and luciferase‐based activity assays indicated that the −475 to −443bp region of HOTAIR promoter contained a crucial regulatory element. Transcription factor prediction with software TRANSFAC revealed that nuclear factor‐κB signaling protein p65 had a binding site in this region and might have roles in HOTAIR expression. The binding of phosphor‐p65 to HOTAIR promoter was verified by chromatin immunoprecipitation, and succeeding experiment results demonstrated that p65 reduction by p65 small interfering RNA and TIPE2 overexpression also decreased HOTAIR expression. Conclusively, our results suggest that HOTAIR was associated with nonresolving inflammation, and its expression is regulated by p65. Abstract : Our results suggest that HOX transcript antisense RNA (HOTAIR) was associated with nonresolving inflammation, and its expression is regulated by p65.